Religiosity Improvement and Development of Islamic Spirit Case Study of Lecturers and Education Personnel in Universitas Islam Bandung - Edi Setiadi; M. Rahmat Effendi; Nandang H.M.Z; Riza Hernawati (Universiti Sains Islam Malaysia, 2024)
Vol. 22 No. 2 (2020): Journal of Islamic Social Sciences and Humanities (Special Issue)